Recommendations for the use of the Maguerez Arch in undergraduate Nursing education: Scoping review (Research, Society and Development, 2024)
Objective: to map information and/or recommendations to support nursing undergraduate teachers regarding the use of the active methodology of the Maguerez Arch. Method: This is a Scoping Review with a protocol registered in the Open Science Framework under number: 10.17605/OSF.IO/GXTD5. The databases accessed were Latin American Literature, Nursing Database, Cumulative Index to Nursing and Allied Health Literature, Cochrane Library, Embase, PubMed/Medical Literature Analysis and Retrieval System Online, Scientific Electronic Library Online, Scopus, Web of Science, and Google Scholar. The inclusion criteria established were: materials in Portuguese, English, or Spanish. No time frame was defined. Exclusion: materials not available in full. Results: a total of 305 studies were identified. Nine articles comprised the final sample of this review. The most prevalent database was Google Scholar. The use of the Maguerez Arch was identified in experience reports, highlighting the fragility with which the use of the Maguerez Arch has been separated from the use of a transformative problem-solving methodology, as well as the difficulty that teachers have in using the educational strategy. Final considerations: Current scientific evidence has identified that the Maguerez Arch provides students with a humanizing praxis, based on respect for differences, mobilizing students to develop an attitude directed towards social practice, as well as instigating clinical reasoning, creating paths for comprehensive patient care through the ability that students can obtain in identifying weaknesses and potentialities in solving real problems and conflicts.